2006
DOI: 10.2134/jnrlse2006.0101
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Planning Education: Utilizing a Design Charrette for Rural Children

Abstract: Although there are efforts underway to educate the public on landscape planning and land management, educational efforts geared toward children have been limited. This study recognizes the importance of landscape planning education, children's inherent spatial cognition, and their observational and creative skills. However, there are limited opportunities for children to be landscape planners and the elements children believe are important in the design and planning of their ideal community are unknown. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Children are keen observers of their environmental setting and are capable of analyzing and understanding their surrounding landscape (Horelli and Kaaja 2002;Moore, Goltsman, and Iacofano 1987;Lynch 1977). While Piaget (1967) found that children were capable of producing two-dimensional representations of a model village, other planning researchers have found that children were capable of producing threedimensional models (Machemer 2006;Horelli and Kaaja 2002). Horelli and Kaaja (2002, 191) note that young people in Finland, Switzerland, and France are keen analysts of their settings, creative producers of ideas for planning, and able to apply planning-enabling tools.…”
mentioning
confidence: 99%
“…Children are keen observers of their environmental setting and are capable of analyzing and understanding their surrounding landscape (Horelli and Kaaja 2002;Moore, Goltsman, and Iacofano 1987;Lynch 1977). While Piaget (1967) found that children were capable of producing two-dimensional representations of a model village, other planning researchers have found that children were capable of producing threedimensional models (Machemer 2006;Horelli and Kaaja 2002). Horelli and Kaaja (2002, 191) note that young people in Finland, Switzerland, and France are keen analysts of their settings, creative producers of ideas for planning, and able to apply planning-enabling tools.…”
mentioning
confidence: 99%